Beyond successful and active ageing : a theory of model ageing - Timonen, Virpi (Bristol, UK : Policy Press, 2016)
This controversial book argues that concepts such as 'successful' and 'active' ageing are potentially dangerous paradigms that reflect and exacerbate inequalities in older populations. Essential reading for anyone seeking to make sense of social constructions of ageing in contemporary societies.
Title from publisher's bibliographic system (viewed on 01 Sep 2022).
Keywords: Population aging -- Social aspects; Older people -- Care